2016
DOI: 10.1111/codi.13138
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy of the perineal body in relation to abdominoperineal excision for low rectal cancer

Abstract: Aim Dissection of the perineal body (PB) during abdominoperineal excision (APE) for low rectal cancer is often difficult due to the lack of a natural plane of dissection. Understanding the PB and its relation to the anorectum is essential to permit safe dissection during the perineal phase of the operation and avoid damage to the anorectum and urogenital organs. This study describes the anatomy and histology of the PB relevant to APE. Method Six human adult cadaver pelvic exenteration specimens (three male, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 17 publications
1
14
0
1
Order By: Relevance
“…As demonstrated in this study (Fig. 3a), some superficial fibres from the longitudinal rectal muscle contribute to the perineal body as shown by others [34] and project longitudinally or transversely to become continuous with the adipose fibrous meshwork within the prerectal space. It is therefore entirely plausible that mechanical stresses caused by rectal mobilization contribute to different configurations seen in the prerectal space [11].…”
Section: Discussionsupporting
confidence: 74%
“…As demonstrated in this study (Fig. 3a), some superficial fibres from the longitudinal rectal muscle contribute to the perineal body as shown by others [34] and project longitudinally or transversely to become continuous with the adipose fibrous meshwork within the prerectal space. It is therefore entirely plausible that mechanical stresses caused by rectal mobilization contribute to different configurations seen in the prerectal space [11].…”
Section: Discussionsupporting
confidence: 74%
“…For example, stretching of the perineal body during pregnancy does not substantially impact defecatory, urinary or reproductive muscle function (Meriwether et al, ). Similarly, surgical dissection through the perineal body does not adversely affect the functions of superficial perineal muscles in either males or females (Kraima et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…13 Thin-sliced magnetic resonance imaging (MRI) and cadaver dissection studies has shown that the bulbocavernosus muscle, the superficial and deep transverse perineal muscle, the internal and external anal sphincters as well as the puboperinealis and puboanalis portions of the puborectalis muscle all attach to the perineal body. [14][15][16] The bulbocavernosus muscles cover the superficial parts of the vestibular bulbs and the major vestibular glands. They consist of striated muscles 15,17 and run from the body of the clitoris, beneath the labia majora surrounding the vaginal orifice, inserting in the upper and lateral part of the perineal body.…”
Section: The Perineal Body and The Urogenital Diaphragmmentioning
confidence: 99%
“…[14][15][16] The bulbocavernosus muscles cover the superficial parts of the vestibular bulbs and the major vestibular glands. They consist of striated muscles 15,17 and run from the body of the clitoris, beneath the labia majora surrounding the vaginal orifice, inserting in the upper and lateral part of the perineal body. 18 By contracting they cause a narrowing of the vaginal orifice and by compressing the deep dorsal vein of the clitoris, they contribute to female erection.…”
Section: The Perineal Body and The Urogenital Diaphragmmentioning
confidence: 99%